Administração oral de probiótico com células viáveis e inativadas em leitões - Busanello, Marli (2011)
The objective was to evaluate the use oral probiotic of with viable cells and inactivated ("pool" of Lactobacillus sp. and Lactobacillus plantarum of gastrointestinal origin of pigs), on performance, intestinal microbiota and the immune system of piglets during the stages of lactation and creche. Were used, 108 lactating piglets and for nursery phase 72 piglets weaned at 21 days old, divided into an experimental design of randomized blocks with three treatments and six replicates. The treatments were: Treatment A: 1 ml of MRS broth + 1 ml of sterile saline, treatment B: 1 ml of probiotic (8.60 X 107 CFU/ml of a "pool" of Lactobacillus plantarum and Lactobacillus sp) activated MRS broth + 1 ml of saline, treatment C: 1 ml of probiotic inactivated cells in MRS broth + 1 ml of saline. Treatments were administered orally to piglets in the daily morning, from birth to 35 days of age with 1 ml per animal lactating and 2 ml in the nursery phase. The count of acidoláticas bacteria, and coliforms were not affected (P> 0.05) by treatments and sampling times. There was no effect (P>0.05) of treatments for weight gain and weight gain daily of piglets from birth to 21 days old. From 21 to 35 days of age was observed lower consumption and lower daily feed intake (P<0.05) for the control treatment when compared to the probiotic treatments and greater weight gain and weight daily gain (P<0.05) was observed in probiotic treatment with cells inactivated in relation to probiotic treatment with viable cells and control. There was less concentration (P<0.05) globulin in the treatment with probiotics compared to control. There were no significant differences (P>0.05) for the variables serum protein, albumin, glucose, hemoglobin, leukocytes, hematocrit, red blood cells, eosinophils, sticks, segments, lymphocytes, monocytes, platelets and serum levels of IgA between treatments. It was concluded that oral use of probiotics with viable cells and inactivated did not alter microbial counts, the values of serum protein, albumin, glucose, blood count and IgA and use of probiotics with viable and inactivated cells diminished serum globulin